Study on the influence of ketogenic diet and intermittent fasting on the change of body fat rate - Yu, Puyuan (Transactions on Materials, Biotechnology and Life Sciences, 2024)
The purpose of this study is to explore the influence of ketogenic diet and intermittent fasting on the change of body fat rate, and to provide more scientific and effective methods for obese people to lose weight. Through randomized controlled trial design, 120 overweight or obese subjects were recruited and randomly divided into four groups for 12 weeks of dietary intervention. The control group kept their daily eating habits, while the ketogenic diet group adopted a diet scheme of high fat, low carbohydrate and moderate protein. The intermittent fasting group chose two days a week for light fasting, while the combined group used ketogenic diet and intermittent fasting at the same time. The research results show that both the ketogenic diet group and the intermittent fasting group can effectively reduce the weight and body fat percentage of the subjects, and the combination of the two has the most significant effect. The ketogenic diet group showed the greatest decrease in body weight and body fat percentage, at -3.5 ± 1.2kg and -4.8 ± 1.5%, respectively, while the combined group showed a more significant decrease, reaching -4.7 ± 1.4kg and -6.3 ± 1.8%, respectively. Regression analysis shows that ketogenic diet, intermittent fasting and their combination have significant effects on body fat rate, and the increase of weekly exercise time is also significantly related to the decrease of body fat rate. The study also found that ketogenic diet and intermittent fasting have their own advantages in reducing body fat rate, but they may also bring certain health risks, such as hypoglycemia and ketoacidosis. Therefore, doctors or nutritionists should tailor the diet plan according to individual conditions and pay attention to its potential side effects. This study provides a new weight loss option for obese people and provides a direction for future research.